Evidence for Underregistration of Suicide - M. A. Riedinger; R. F. P. de Winter (Case Reports in Psychiatry)
In this case report, we will present two cases in which the Dutch municipal coroner registered a natural death, but treating psychiatrists doubted the validity of this decision on the grounds of clinical data and investigation. For both cases, we present evidence that deaths likely resulted from suicide, raising serious doubts about the accuracy of the registered cause of death. According to the WHO bulletin on suicide prevention, the national registration of suicide is unsatisfactory in many countries. The Netherlands is listed by the WHO as having one of the most accurate registration procedures. Nevertheless, there are indications that national registration, even in the Dutch system, is not infallible. In this case report, we present several ways in which the registration process is liable to error and evidence for underregistration of suicide rates.